The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2010
DOI: 10.1590/s0001-37652010005000001
|View full text |Cite
|
Sign up to set email alerts
|

Population structure of the gomphothere Stegomastodon waringi (Mammalia: Proboscidea: Gomphotheriidae) from the Pleistocene of Brazil

Abstract: The Quaternary fossil record of Águas de Araxá (QAA) is represented mainly by an accumulation of skeletal elements of several sizes, which are assigned to a population of Stegomastodon waringi. We analyzed 97 molars according to the wear stages of Simpson and Paula-Couto (1957), and developed a morphometric wear index. The population structure (proportion of immature, subadult, adult, mature adult and senile adult individuals) was identified, and these five age classes were compared to those of extant elephant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 11 publications
1
10
0
Order By: Relevance
“…The QAA N. platensis had been previously recognized as a single population (Simpson and Paula Couto, 1957;Mothé et al, 2010) and its age was established by dating a single tooth (DGM104-M) and its associated sediment, representing the dating for the entire population. This N. platensis tooth is currently housed at the paleontological collection of Departamento Nacional de Produção Mineral, Rio de Janeiro State, Brazil.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The QAA N. platensis had been previously recognized as a single population (Simpson and Paula Couto, 1957;Mothé et al, 2010) and its age was established by dating a single tooth (DGM104-M) and its associated sediment, representing the dating for the entire population. This N. platensis tooth is currently housed at the paleontological collection of Departamento Nacional de Produção Mineral, Rio de Janeiro State, Brazil.…”
Section: Methodsmentioning
confidence: 99%
“…Gomphotheres fossils have been found in almost all Brazilian states, but the Quaternary of Águas de Araxá (QAA) outcrop is noted for its great abundance of dental and postcranial fossils of N. platensis (Simpson and Paula Couto, 1957;Mothé et al, 2010). Previous studies suggested that the gomphothere remains from the QAA outcrop represents a single N. platensis population (Simpson and Paula Couto, 1957;Mothé et al, 2010). These papers are the basis for several other studies that investigated aspects of the taphonomy and paleoecology of South American gomphotheres (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Following this idea, the biomass of herbivore communities is closely regulated by food availability (i.e. habitat's carrying capacity; see a study with African ungulates in Fritz and Duncan, 1994) and, in accordance with Mothé et al (2010), the family structure of Notiomastodon is analogous to those from current African elephants (Loxodonta africana). Also, Thomas et al (2008) show that summer home range (environmental requirements) of current African elephants is four times wider than its winter one.…”
Section: Cuvieronius Notiomastodonmentioning
confidence: 99%
“…Width reaches 75 mm at the level of the third raw, 67 mm at the fourth and 47.5 mm at the heel.This gomphothere had the mass of an Asian elephant. It is reported from several Brazilian sites such as Águas de Araxá (Minas Gerais) (Mothé et al, 2010), Lagoa São Vitor (Piauí) and Lagoa Uri de Cima (Pernambuco state) (Faure & Guérin, 2013, Figures 3 and 4). Recently, Mothé et al (2020) observed some traces of projectile points on a Gomphothere calf skull from Lapa do Caetano (Lagoa Santa region, Minas Gerais state).…”
Section: Resultsmentioning
confidence: 92%